1996
DOI: 10.1007/bf01702605
|View full text |Cite
|
Sign up to set email alerts
|

The voluntary community health movement in India: A strengths, weaknesses, opportunities, and threats (SWOT) analysis

Abstract: There has been a prolific growth of voluntary organizations in India since independence in 1947. One of the major areas of this growth has been in the field of community health. The purpose of this article is to historically trace the voluntary movement in community health in India, analyze the current status, and predict future trends of voluntary efforts. A review of the literature in the form of a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis was the method of this study. Some of the key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 3 publications
0
28
0
2
Order By: Relevance
“…This approach to obtain information is crucial for building theory based health education intervention strategy for behavior change which is a definitive need for health education intervention in India. [16] Thus, there is a need of behavior change communication strategy based on indigenous concerns and addressing socio-cultural barriers by reinforcing locally existing channels of communication to break away isolation and build interactive village level networks. [17] The intervention strategy focusing on advocacy and implementation of anti tobacco law, community based health education of parents & non school going children/ school drop-outs and school based education through teachers would be appropriate for rural settings of developing countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach to obtain information is crucial for building theory based health education intervention strategy for behavior change which is a definitive need for health education intervention in India. [16] Thus, there is a need of behavior change communication strategy based on indigenous concerns and addressing socio-cultural barriers by reinforcing locally existing channels of communication to break away isolation and build interactive village level networks. [17] The intervention strategy focusing on advocacy and implementation of anti tobacco law, community based health education of parents & non school going children/ school drop-outs and school based education through teachers would be appropriate for rural settings of developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…[6] There is a need for locally relevant community based data regarding tobacco use pattern among adolescents, their perceptions and behaviors for designing effective community based intervention strategy. Hence, the objectives of the present study were to generate community based data on tobacco use pattern among rural adolescents (15)(16)(17)(18)(19) 101 CMYK years) and to find out reasons for use and non use of tobacco products.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the SWOT analysis method can help define the user's needs, the characteristics of the assistive device and the environmental conditions required to foster independence. Sharma used the SWOT analysis F o r P e e r R e v i e w 3 to analyse literature on evaluations of community-based rehabilitation programmes [21]. He reported that many evaluations were conducted in community settings and many novel data collection techniques were used, both perceived as strengths in the context of his study.…”
Section: Introductionmentioning
confidence: 99%
“…Accurately capturing time estimates and developing standards of work can help increase workflow efficiency and functionality by reducing/eliminating non-value-added activities while providing high quality care in a healthcare system. [11] Strengths-Weaknesses-Opportunities-Threats (SWOT) analysis [12,13] is a QI tool used in studies throughout the world [12,[14][15][16][17][18] to inform improvement efforts in a variety of healthcare settings and populations such as traumatic brain injury, [14] pediatric rehabilitation, [15] community health, [16] oral healthcare, [17] and geriatric care in the military. [19] In our study, facility staff and Veterans' perspectives were col-lected to determine the strengths and weaknesses of the ECUs as well as their opportunities and threats.…”
Section: Methodsmentioning
confidence: 99%